Pig Is Money Aremag (Funerals) among the Ibaloy of Upper Loacan (Itogon, Benguet) - Laugrand, Frederic; Laugrand, Antoine; Magapin, Gliseria; Tamang, Jazil (2021)
Among the rituals of the Ibaloy of the Philippine Cordillera, the aremag, the first funeral cycle, prepares a person’s departure to the next world. Drawing on several projects designed to share the elders’ traditional knowledge with the youth in Upper Loacan in Benguet, we analyze specifically the killing of the pig and its squeal that mark a transfer of vitality and allow a series of transactions. The pig’s meat embodies the notion of money: wealth for the deceased and inheritance, luck, bountiful harvests, or gold ore for the living who provide the pigs. Aremag testifies to how rituals participate in Ibaloy cultural resistance.
Keywords: Death and burial; Funerals; Indigenous peoples; Benguet; Cordillera region